Efficient and convenient heterogeneous Cu/MCM-41 catalyst for the synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives - Dhengale, Shankar D.; Bhosale, Tanaji R.; Shinde, Sachin B.; Rode, Chandrashekhar V.; Kolekar, Govind B.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2023)
An efficient and convenient method for synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives using Cu/MCM-41 (20 mg) as heterogeneous catalyst. The advantages have an excellent product yield within a short time and easy work-up procedure, and the products have directly recrystallized from hot methanol with cost-effective catalyst. One-pot three-component reaction from aromatic aldehydes, cyclic 1,3-dicarbonyl compounds, and 1-naphthyl amine has been carried under ethanol as a solvent with reflux condition. Moreover, the catalyst can be recovered conveniently and reused efficiently, and recyclable. [GRAPHICS] .
Keywords: Benzo[c]acridine; dimedone; Heterogeneous Cu/MCM-41 catalyst; Multicomponent one-pot reaction